Coupled Toroidal Dipole Modes in Silicon Nanodisk Metasurface: Polarization Independent Narrow Band Absorption and Directional Emission. Issue 22 (21st September 2020) - Hasebe, Hiroaki; Sugimoto, Hiroshi; Hinamoto, Tatsuki; Fujii, Minoru
Abstract: Besides the fundamental Mie resonance modes of high‐index dielectric nanostructures, an extended multipole family, i.e., toroidal multipoles, provide great opportunities for engineering a new class of nanophotonic devices. Here, it is demonstrated theoretically and experimentally that a hexagonal array of circular silicon (Si) nanodisks (NDs) supports intra‐ and inter‐ND toroidal dipole (TD) modes. The key concept is the alignment of Si NDs near the anapole state condition for constructive interaction of the TD modes between neighboring NDs. Numerical simulation reveals that strong field confinement by the coupled TD modes enhances the absorption 120‐fold at the resonance wavelength compared to that of a flat Si film with the same thickness. In this study, macroscopic scale hexagonal Si ND arrays are fabricated using a colloidal lithography, and spectrally selective absorption enhancement due to the TD modes is demonstrated. Furthermore, it is demonstrated that a dipolar emitter can also excite TD modes, which modify the spectral shape and the directionality of the emission. Abstract : This work presents a hexagonal silicon nanodisk array supporting coupled toroidal dipole modes and experimentally demonstrates toroidal‐mode‐induced, spectrally‐selective absorption enhancement up to 30 times with respect to a flat silicon film. The toroidal mode of silicon nanodisks can couple with a dipolar emitter and modify the spectral shape and the directionality of the emission.